2019
DOI: 10.1021/acs.nanolett.8b04681
|View full text |Cite
|
Sign up to set email alerts
|

Nanomagnetism of Magnetoelectric Granular Thin-Film Antiferromagnets

Abstract: Antiferromagnets have recently emerged as attractive platforms for spintronics applications, offering fundamentally new functionalities compared to their ferromagnetic counterparts. While nanoscale thin film materials are key to the development of future antiferromagnetic spintronics technologies, experimental tools to explore such films on the nanoscale are still sparse. Here, we offer a solution to this technological bottleneck, by addressing the ubiquitous surface magnetisation of magnetoelectic antiferroma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 48 publications
7
77
0
Order By: Relevance
“…If the only contribution to the internal field at the muon site were the monopolar field from the magnetoelectric response, we would expect the shifts in both cases to be in the same direction, since both sets of measurements are performed on the same magnetoelectric domain. It is known, however, that Cr 2 O 3 thin films can have stray spins caused by defects at the interface with the Al 2 O 3 substrate, as well as impurity spins at the interface, which have been shown to be susceptible to small magnetic fields in thin film samples 28,30 . (Note that the intrinsic surface spin density resulting from the termination of the antiferromagnetic magnetoelectric [31][32][33] is not reversed under the conditions of our experiment, since this would require the reversal of the full antiferromagnetic domain 33 .…”
Section: B Resultsmentioning
confidence: 99%
“…If the only contribution to the internal field at the muon site were the monopolar field from the magnetoelectric response, we would expect the shifts in both cases to be in the same direction, since both sets of measurements are performed on the same magnetoelectric domain. It is known, however, that Cr 2 O 3 thin films can have stray spins caused by defects at the interface with the Al 2 O 3 substrate, as well as impurity spins at the interface, which have been shown to be susceptible to small magnetic fields in thin film samples 28,30 . (Note that the intrinsic surface spin density resulting from the termination of the antiferromagnetic magnetoelectric [31][32][33] is not reversed under the conditions of our experiment, since this would require the reversal of the full antiferromagnetic domain 33 .…”
Section: B Resultsmentioning
confidence: 99%
“…For example, the stray fields of the single layer uncompensated spins on the surface of Cr 2 O 3 were imaged by scanning nitrogen-vacancy (NV) center microscopy, which allowed to measure the reorientation of the AFM order parameter across the domain wall with sub-100 nm spatial resolution. 94 This impressive sensitivity to the local magnetization is achieved by attaching a diamond nanocrystal to the atomic force microscopy tip. The NV centers exhibit a Zeeman splitting according to the local magnetic field, which can thus be measured with high magnetic and spatial resolution.…”
Section: Introduction To Afm Domains and Domain Wallsmentioning
confidence: 99%
“…4(c)&(d)). This behavior is in strong contrast to magnetometry with non-OOP oriented scanning NV centers [5,6,8,9], where the qualitative behavior of B NV near sample edges depends strongly on the orientation of the edge (Fig. 4(b)).…”
mentioning
confidence: 62%
“…Our results will be impactful for scanning NV magnetometry in general and for applications in spintronics and the investigation of thin film magnets in particular.Scanning probe magnetometry using nitrogen-vacancy (NV) center electronic spins in diamond offers a unique combination of spatial resolution, magnetic field sensitivity and quantitative magnetic imaging [1,2]. These combined performance characteristics have led to room-temperature imaging of single electron spins [3], nanoscale domains in multiferroics [4] and antiferromagnets [4,5], and to cryogenic experiments addressing superconductors [6-8] and magnetism in atomically thin crystals [9]. These and other studies have demonstrated how scanning NV magnetometers can yield valuable insights into materials of high scientific and technological interest, beyond the capacity of existing nanoscale imaging methods.Magnetometry based on NV center spins [10] builds on the extraordinary properties of this point defect in diamond that consists of a nitrogen atom adjacent to a lattice vacancy ( Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation